Factors associated with abandonment of therapy by children diagnosed with solid tumors in Peru - Vasquez, L (2018)
Background: Abandonment of treatment is a major cause of treatment failure and poor survival in children with cancer in low- and middle-income countries. The incidence of treatment abandonment in Peru has not been reported. The aim of this study was to examine the prevalence of and factors associated with treatment abandonment by pediatric patients with solid tumors in Peru. Methods: We retrospectively reviewed the sociodemographic and clinical data of children referred between January 2012 and December 2014 to the two main tertiary centers for childhood cancer in Peru. The definition of treatment abandonment followed the International Society of Paediatric Oncology, Paediatric Oncology in Developing Countries, Abandonment of Treatment recommendation. Results: Data from 1135 children diagnosed with malignant solid tumors were analyzed, of which 209 (18.4%) abandoned treatment. Bivariate logistic regression analysis showed significantly higher abandonment rates in children living outside the capital city, Lima (forest; odds ratio [OR] 3.25; P < 0.001), those living in a rural setting (OR 3.44; P < 0.001), and those whose parent(s) lacked formal employment (OR 4.39; P = 0.001). According to cancer diagnosis, children with retinoblastoma were more likely to abandon treatment compared to children with other solid tumors (OR 1.79; P = 0.02). In multivariate regression analyses, rural origin (OR 2.02; P = 0.001) and lack of formal parental employment (OR 2.88; P = 0.001) were independently predictive of abandonment. Conclusion: Treatment abandonment prevalence of solid tumors in Peru is high and closely related to sociodemographical factors. Treatment outcomes could be substantially improved by strategies that help prevent abandonment of therapy based on these results.